Pharmacological impact of antiretroviral therapy on platelet function to investigate human immunodeficiency virus‐associated cardiovascular risk. (14th March 2019) - Taylor, Kirk A.; Smyth, Erica; Rauzi, Francesca; Cerrone, Maddalena; Khawaja, Akif A.; Gazzard, Brian; Nelson, Mark; Boffito, Marta; Emerson, Michael
Abstract : Background and purpose: Some clinical studies have reported increased myocardial infarction in people living with human immunodeficiency virus (HIV) taking the antiretroviral abacavir sulphate (ABC). Given that clinical studies contain confounding variables (e.g., HIV‐associated factors), we investigated the pharmacological effects of antiretrovirals on platelet function in HIV‐negative volunteers in order to identify mechanisms of increased cardiovascular risk. Experimental approach: Platelets were isolated from healthy volunteers and HIV‐negative subjects enrolled on a Phase I clinical trial and platelet function evaluated using aggregometry and flow cytometry. In vivo platelet thromboembolism was monitored in anaesthetized mice. Key results: Human platelet aggregation was unaffected by all antiretrovirals tested, but ABC treatment led uniquely to increased platelet granule release. ABC also interrupted NO‐mediated inhibition of platelet aggregation and increased in vivo aggregation in mice. Another antiretroviral, tenofovir, did not affect platelet function. Furthermore, aggregation and activation of platelets isolated from 20 subjects taking clinically relevant doses of tenofovir were comparable to baseline samples. Conclusions and implications: ABC can enhance platelet activation, independently of variables that confound clinical studies, suggesting a potential pharmacological effect that is absent with tenofovir. Mechanistically, we propose that ABC enhances platelet degranulation and interrupts NO‐mediated platelet inhibition. The interaction of ABC with NO signalling is demonstrated by ABC‐mediated enhancement of aggregation in vivo and in vitro that persisted in the presence of NO. Although an association between ABC and platelet activation has not been confirmed in patients, these findings provide evidence of a mechanistic link between platelet activation and antiretroviral therapy.